Visual evoked potentials and MBP gene expression imply endogenous myelin repair in adult rat optic nerve and chiasm following local lysolecithin induced demyelination - Mozafari, Sabah; Sherafat, Mohammad Amin; Javan, Mohammad; Mirnajafi-Zadeh, Javad; Tiraihi, Taki (Brain research, 2010)
Multiple sclerosis (MS) patients may suffer from optic disturbances. Toxin-induced demyelinations have frequently been developed to investigate the cellular and structural aspects of demyelination and remyelination processes, separately. The present study describes functional consequence of lysolecithin (LPC)-induced lesion in the adult rat optic nerves and chiasm by recording the visual evoked potentials (VEPs) from the visual cortex and its correlation with myelin basic protein (MBP) expression in lesion site. Records of VEP were obtained at 2, 7, 14 and 28days post-injection. We observed that the VEPs generated by light stimuli progressively changed in both amplitude and latency after the lesion as well as in comparison with those generated in control animals. These observations were confirmed through measurement of mRNA expression level for MBP which is one of the important genes expressed in mature oligodendrocytes and Schwann cells. The level of MBP mRNAs in demyelinated chiasm and optic nerves decreased following lysolecithin injection with its least value on day 7, and then it increased to the control level 14days post-lesion. However, it continued to increase even after that and reached a maximum level 28days post lesion. Results of the present paper show that, LPC injection in the chiasm share functional and molecular alterations which are found in demyelinating disorders in both the optic nerves and chiasm and also these alterations were coming back to level of control animal on 28days post lesion, which is typically seen in myelin repair process. The present paper provides new insights into the experimental toxin-induced models that may be useful for evaluating the functional recovery of demyelinated optic nerves and chiasm following various repairing strategies. It also seems to be useful for studying the protective or remyelinating effects of different therapies in e.g. optic apparatus which is more affected by MS. ►Lysolecithin injection into the optic chiasm causes alterations in VEP records. ►VEP records confirmed endogenous myelin repair. Changes in ►VEP records are correlated with the expression of myelin basic protein. ►VEP records provide useful evaluating tool for the efficacy of myelin repair strategies.